Segregation distortion in myotonic dystrophy. Issue 12 (December 1998) - Magee, A C; Hughes, A E
Abstract : Myotonic dystrophy (DM) is an autosomal dominant disease which, in the typical pedigree, shows a three generation anticipation cascade. This results in infertility and congenital myotonic dystrophy (CDM) with the disappearance of DM in that pedigree. The concept of segregation distortion, where there is preferential transmission of the larger allele at the DM locus, has been put forward to explain partially the maintenance of DM in the population. In a survey of DM in Northern Ireland, 59 pedigrees were ascertained. Sibships where the status of all the members had been identified were examined to determine the transmission of the DM expansion from affected parents to their offspring. Where the transmitting parent was male, 58.3% of the offspring were affected, and in the case of a female transmitting parent, 68.7% were affected. Studies on meiotic drive in DM have shown increased transmission of the larger allele at the DM locus in non-DM heterozygotes for CTGn. This study provides further evidence that the DM expansion tends to be transmitted preferentially.